Exploring demotivating factors among EFL learners across differing levels of English proficiency in blended learning settings - Wenjing Zhou; Esther Jawing; Veronica Petrus Atin; Xiaoqi Deng; Sufang Zeng; Yan Zhan (Elsevier B.V., 2025)
This study analysed the demotivating factors perceived by English as a foreign language (EFL) learners across different levels of English proficiency in a blended learning context. The analysis was conducted through a questionnaire survey undertaken by 649 EFL sophomore students with varied majors from a university in mid-east China. Cronbach's alpha reliability coefficients were calculated to evaluate the internal consistency of the questionnaire items, and principal component factor analysis was performed to explore the structural validity of the questionnaire. Descriptive statistics were employed to illustrate the profiles of the questionnaire items and the demotivating factors. An analysis of variance (ANOVA) and post-hoc multi-comparison analysis were utilised to determine whether significant differences existed among learners at different English proficiency levels regarding the demotivating factors and to determine the differences. Results revealed that an inappropriate learning environment was the greatest contributor to learners' demotivation, while loss of task value was considered the least demotivating. Moreover, low-proficiency learners were more likely to be demotivated by internal factors than high-proficiency learners, whereas high-proficient learners were more inclined to attribute their demotivation to internal factors. It is implicated that EFL educators should strategically diversify instructional content and pedagogical approaches to maintain learner immersion within blended educational settings, and that different strategies ought to be employed to enhance learning motivation for low proficient and high proficient EFL learners.